PSSE: Parenting Style Sex Education, on Understanding Sexual Violence What Parents Do Towards Children in Tiktok - Fitri, Azalia Cahya Gita; Putri, Dhea Anggraeni; Desyasti, Falaah Azurra; Humaira, Lenggogeni Trity; Syakuuron, Muhammad Abdan; Yohana, Nining Ni'mah; Briana, Regina Fajari (Tarqabin Nusantara Group, 2023)
Child sexual abuse is the involvement of children in all forms of sexual activity that occurs before the child reaches the age limit set by state law and is carried out by adults or older people for sexual pleasure. Based on data from the Online Information System for the Protection of Women and Children in 2023, the highest number of cases of violence based on the place of occurrence occurred in the household sphere, which amounted to 15,450 cases with the most experienced type of violence being sexual violence at 11,191 cases. The purpose of this study is to provide information and education about